PERGESERAN PUSAT KEGIATAN UPACARA DI SITUS MEGALITIK PUNCAK GUNUNG LAWU - Sulistyarto, Priyatno Hadi (Berkala Arkeologi, 1999)
The megalithic structures on the peak of Mount Lawu are still used as places of worship by the people around Mount Lawu. This shows a tradition of worshiping ancestral spirits who use megalithic buildings as a means of worship ceremonies. It is very interesting that in today's worship ceremonies, the center of the ceremony is no longer in the Argo Dumilah but in the Argo Dalem Timur. In fact, based on the location of the distribution of structures, Argo Dalem Timur is located in a non-central stucture position or located around the central structure. This shows a shift in the center of the worship ceremony from the Argo Dumilah to the Argo Dalem Timur.